Effect Of Yoga Intervention on Pre And Post Yoga Intervention Depression Levels - Neha Vasisht; Dr. Sandeep Kumar Singh; Sh. Mohan Kumar Karki; Dr. Surender Singh (Revista Electronica de Veterinaria, 2024)
Depression is a global health issue that affects so many individuals, therefore requiring both efficacious and accessible solutions. These traditional treatments can provide assistance but may also suffer from drawbacks, including expense, adverse effects, and social stigma. This study investigates an alternative approach; the use of yoga as a non-pharmacological intervention to alleviate symptoms of depression, for individuals that are only mildly to moderately symptomatic.The six-week integrated yoga program included physical postures, breathing exercises and mindful meditation practices aimed at enhancing the mental well-being. To gauge the influence, the researchers deployed the Beck Depression Inventory-II (BDI-II), an established depression assessment tool. A control group used in the pretest-posttest experimental design was used in this study.